Transitivity and Context of The Situation in The News Text - Khusnul Aisaro; Suhardi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This study aims to describe the study of Systemic Functional Linguistics (SFL) about the transitivity process system and the state of the news text situation. The source of data in this study is the news text in the Indonesian textbook published in 2021 at the junior high school /MTs class VII level. Data collection is carried out by reading and recording. This research is a descriptive research with a qualitative approach. Based on the findings and analysis of the study, several conclusions can be made. First, researchers found transitivity consists of five types of processes, namely material processes, mental processes, relational processes, verbal processes, and existential processes. Second, participants consist of recipients or clients. Third, circumcision consists of range, location, way, cause, environment, problem, role, inclusion, view. Fourth, the context of the situation consists of the terrain of discourse, the involvement of discourse, and the means of discourse.